2022
DOI: 10.5852/ejt.2022.833.1881
|View full text |Cite
|
Sign up to set email alerts
|

A morphometric approach and recircumscription of the Stachytarpheta longispicata complex (Verbenaceae)

Abstract: The Stachytarpheta longispicata complex is a group of seven accepted infraspecific taxa endemic to the Brazilian Cerrado, defined by its pedicellate flowers with salmon or dark red corollas. Due to the great morphological variation and very brief original descriptions, these taxa have controversial circumscriptions. We evaluated the morphological variation through the morphometric analysis of 11 natural populations in addition to nomenclatural types to assess the current infraspecific circumscriptions and clar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Furthermore, it was not possible to collect populations from Serra Dourada and Jalapão (Cardoso unpubl.). Still, after clarifying the limits of the S. longiospicata complex (Cardoso et al 2022), morphological analyses confirmed that the plants from Serra Dourada and Jalapão are distinct within Stachytarpheta , being proposed herein as new species.…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…Furthermore, it was not possible to collect populations from Serra Dourada and Jalapão (Cardoso unpubl.). Still, after clarifying the limits of the S. longiospicata complex (Cardoso et al 2022), morphological analyses confirmed that the plants from Serra Dourada and Jalapão are distinct within Stachytarpheta , being proposed herein as new species.…”
Section: Introductionmentioning
confidence: 68%
“…Regarding the morphological characters of the Stachytarpheta inflorescence, almost all species present sessile flowers (inflorescences in spikes), except a small group endemic to the Brazilian Cerrado domain, characterised by having pedicellate flowers (inflorescences in racemes) (Atkins 2005, Cardoso and Salimena 2020, Cardoso et al 2022). This group of pedicellate flowers includes, according to Atkins (2005), seven infraspecific taxa (three varieties and four subspecies) of Stachytarpheta longispicata (Pohl) S.Atkins.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations